2007
DOI: 10.1364/oe.15.017443
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-enhanced laser absorption spectroscopy using microresonator whispering-gallery modes

Abstract: Tunable diode laser absorption spectroscopy using microresonator whispering-gallery modes (WGMs) is demonstrated. WGMs are excited around the circumference of a cylindrical cavity 125 mum in diameter using an adiabatically tapered fiber. The microresonator is very conveniently tuned by stretching, enabling the locking of an individual WGM to the laser. As the laser is scanned in frequency over an atmospheric trace-gas absorption line, changes in the fiber throughput are recorded. The experimental results of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 36 publications
0
56
0
Order By: Relevance
“…However, till now all the demonstrations were implemented in optical laboratories with well-set equipment on bulky optical tables, which limit the practical applications of WGM microresonators, e.g., various kinds of sensing, including sensing of single nanoparticle [4][5][6][7], biomolecule [21,22], magnetic field [23,24], angular velocity [25][26][27], gas [28,29], etc. The obstacles of practical applications for WGM sensors lie on two factors: i) the challenge of long-term stability for tapered fiber coupling of cavity modes outside the laboratory, and ii) bulky commercial equipment needed for testing cavity modes, including not only a laser source and a detector but also a function generator and an oscilloscope.…”
Section: Introductionmentioning
confidence: 99%
“…However, till now all the demonstrations were implemented in optical laboratories with well-set equipment on bulky optical tables, which limit the practical applications of WGM microresonators, e.g., various kinds of sensing, including sensing of single nanoparticle [4][5][6][7], biomolecule [21,22], magnetic field [23,24], angular velocity [25][26][27], gas [28,29], etc. The obstacles of practical applications for WGM sensors lie on two factors: i) the challenge of long-term stability for tapered fiber coupling of cavity modes outside the laboratory, and ii) bulky commercial equipment needed for testing cavity modes, including not only a laser source and a detector but also a function generator and an oscilloscope.…”
Section: Introductionmentioning
confidence: 99%
“…Losses due to absorption or scattering of the evanescent wave outside the resonator will change the Q factor of the resonator. Several groups demonstrated that WGM resonators could be used for absorption sensing in gases and liquids, detection of refractive index changes around the resonator and single molecules on its surface [24,25]. All chemical sensing studies performed until now with WGM used near-IR and visible continuous wave (CW) single frequency lasers because of the wide availability of such lasers and detectors.…”
Section: Applications Of Saturated Absorption and Wgm In The Mid-irmentioning
confidence: 99%
“…The fraction of the WGM's energy in the evanescent field depends on the refractive indices inside and outside resonator. For gas phase sensing, this fraction, f, is only ~1% or less [25]; while for liquid phase, f could be as high as 30% [24]. Therefore, with the Q value of >10 8 in the gas phase and >10 7 in the liquid phase, the effective sensor path length would exceed 1 meter.…”
Section: Wgm Coupling In Caf 2 Ball/discmentioning
confidence: 99%
“…For cylindrical resonators based on a section of optical fiber, there are a number of potential advantages that make such resonators worth exploring: (1) a very simple fabrication process, since optical fibers are highly uniform in diameter, allowing large numbers of identical resonators to be fabricated and providing a high degree of repeatability; (2) optical fibers can be easily manipulated and mounted; and (3) the alignment for optimal coupling of the excitation light into the fiber MR has on only one angular degree of freedom, as opposed to two for experiments involving microspheres [14]. As a result, the optical setup for the cylindrical fiber-based MR experiments is more straightforward.…”
Section: Introductionmentioning
confidence: 99%